2012
DOI: 10.1016/j.ijid.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment of multidrug-resistant osteoarticular tuberculosis: a systematic literature review

Abstract: Osteoarticular MDR-TB is very infrequently reported in the literature. The few cases reviewed suggest that it is possible to achieve a good outcome with second-line anti-tuberculous drugs, and that surgery might be useful for cases in which an optimized medical treatment is not possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…At present, osteoarticular tuberculosis has been treated according to the standard therapy protocol by antitubercular drugs for a minimum of 8 and 20 months for total chemotherapy. 2 However, longer treatment time resulted in patient noncompliance and critical side effects. 3 It is key for the treatment of osteoarticular tuberculosis to increase local drug concentrations for higher therapeutic efficiencies and lower toxicity for body.…”
Section: Introductionmentioning
confidence: 99%
“…At present, osteoarticular tuberculosis has been treated according to the standard therapy protocol by antitubercular drugs for a minimum of 8 and 20 months for total chemotherapy. 2 However, longer treatment time resulted in patient noncompliance and critical side effects. 3 It is key for the treatment of osteoarticular tuberculosis to increase local drug concentrations for higher therapeutic efficiencies and lower toxicity for body.…”
Section: Introductionmentioning
confidence: 99%
“…The results of prolonged medical treatment coupled with surgery gives satisfactory results in most patients [5]. The few cases reviewed of osteoarticular multidrug-resistant tuberculosis have a good outcome with second-line anti-tuberculous drugs combined with surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…No studies have been found assessing amikacin or kanamycin, but other aminoglycosides have a good penetration into synovial fluid and intervertebral discs. [ 11 ]…”
Section: Methodsmentioning
confidence: 99%